Cyclooxygenase-2 Modulates Glycosaminoglycan Production in the Skin During Salt Overload - Agócs, Róbert; Pap, Domonkos; Sugár, Dániel; Tóth, Gábor; Turiák, Lilla; Veréb, Zoltán; Kemény, Lajos; Tulassay, Tivadar; Vannay, Ádám; Szabó, Attila J. (Frontiers in Physiology, 2020)
Sodium (Na+) can accumulate in the skin tissue, sequestered by negatively charged glycosaminoglycans (GAGs). During dietary salt overload, the amount and charge density of dermal GAG molecules – e.g., hyaluronic acid (HA) and chondroitin sulfate (CS) – increases; however, the regulation of the process is unknown. Previously, it has been demonstrated that the level of cyclooxygenase-2 (COX-2) activity and the content of prostaglandin E2 (PGE2) are elevated in the skin due to high-salt consumption. A link between the COX-2/PGE2 system and GAG synthesis was also suggested. We hypothesized that in dermal fibroblasts (DFs) high-sodium concentration activates the COX-2/PGE2 pathway and also that PGE2 increases the production of HA. Our further aim was to demonstrate that the elevation of the GAG content is ceased by COX-2 inhibition in a salt overloaded animal model. For this, we investigated the messenger RNA (mRNA) expression of COX-2 and HA synthase 2 enzymes as well as the PGE2 and HA production of DFs by real-time reverse transcription PCR (qRT-PCR) and ELISA, respectively. The results showed that both high-sodium concentration and PGE2 treatment increases HA content of the media. Sodium excess activates the COX-2/PGE2 pathway in DFs, and COX-2 inhibition decreases the synthesis of HA. In the animal experiment, the HA- and CS disaccharide content in the skin of male Wistar rats was measured using high performance liquid chromatography-mass spectrometry (HPLC-MS). In the skin of rats receiving high-salt diet, the content of both HA‐ and monosulfated-CS disaccharides increased, whereas COX-2 inhibition blocked this overproduction. In conclusion, high-salt environment could induce GAG production of DFs in a COX-2/PGE2-dependent manner. Moreover, the COX-2 inhibition resulted in a decreased skin GAG content of the salt overloaded rats. These data revealed a new DF-mediated regulation of GAG synthesis in the skin during salt overload.